Experimental Investigation of Thermal Performance in a Concentric-Tube Heat Exchanger with Wavy Inner Pipe - Cakmak, Gulsah; Yucel, H. Lutfi; Argunhan, Zeki; Yildiz, Cengiz (Springer/Plenum Publishers, 2012)
In this article, the heat transfer, friction factor, and thermal performance factor characteristics of a concentric-tube heat exchanger are examined experimentally. A wavy inner pipe is mounted in the tube with the purpose of generating swirl flow that would help to increase the heat transfer rate of the tube. The examination is performed for a Reynolds number ranging from 2700 to 8800. An empirical correlation is also formulated to match with experimental data of the Nusselt number using the Wilson plot method. In addition, to obtain the real benefits in using the swirl generator at a constant pumping power, the thermal enhancement factor is also determined. Over the range considered, the increases in the Nusselt number, friction factor, and thermal performance factor are found to be, respectively, about 113 %, 81 %, and 196 % higher than those obtained from a smooth-surface inner pipe.
Keywords: Enhanced heat transfer; Heat exchanger; Wavy inner pipe; Wilson plot method